AN UNDESIRED IMPLICATION FROM GLOBALIZATION: ISIS, AN ADAPTIVE THREAT IN A DORMANT PHASE - Manullang, Abel Josafat; Wicaksono, Raden AP; Sudirman, Arfin (Global: Jurnal Politik Internasional, 2023)
Globalization has brought about numerous changes to the world. However, those changes and advances have also been enjoyed by terrorist groups, one of them is ISIS which uses those things in its terror acts. This article seeks to explain how ISIS has adapted and enhanced its capacity as a result of globalization. Apart from employing the qualitative research method, this article also uses concepts and theories like terrorism, globalization, and James D. Kiras's theory on how globalization enhances terrorism. This article would then proceed to the three matters of ISIS as a threat to national and international security, how ISIS has developed as a result of globalization, and how despite its current state, it is still a threat to reckon with. First, ISIS has shown its uniqueness as a terrorist group in its capacity to adapt to globalization and concern with territories. The latter pushed it to utilize the former to strengthen its grasp on the territories it has taken over. Moving on, ISIS has grown in its mobility, lethality, proselytizing, coordination, and security. Finally, despite its decline, the international community is left with ISIS's remnants as well as the prospect of its reemergence.